2018
DOI: 10.5114/kitp.2018.74670
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative blood morphology and incidence of acute kidney injury after on-pump coronary artery bypass grafting – a single-center preliminary report

Abstract: IntroductionAcute kidney injury (AKI) after coronary artery bypass grafting (CABG) performed in cardiopulmonary bypass (CPB) may complicate the postoperative course and has a negative impact on outcome. In some cases, postoperative AKI develops in spite of normal baseline creatinine concentration and estimated glomerular filtration rate (eGFR).AimTo examine whether there is any association between the preoperative blood morphology and incidence of post-operative AKI.Material and methodsThe study involved 62 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…CSA-AKI after cardiac surgery is also closely related to surgical factors, and studies have shown that HBG concentration during CPB [40,41], hematocrit [42], and CPB time [43,44] are independent risk factors for CSA-AKI after cardiac surgery. This study also showed that operation time, CPB time, aortic cross-clamp time, and intraoperative blood product intake were associated with CSA-AKI after robotic cardiac surgery, and exclusion of confounding factors showed that operation time ≥ 300 min was an independent risk factor for postoperative CSA-AKI, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…CSA-AKI after cardiac surgery is also closely related to surgical factors, and studies have shown that HBG concentration during CPB [40,41], hematocrit [42], and CPB time [43,44] are independent risk factors for CSA-AKI after cardiac surgery. This study also showed that operation time, CPB time, aortic cross-clamp time, and intraoperative blood product intake were associated with CSA-AKI after robotic cardiac surgery, and exclusion of confounding factors showed that operation time ≥ 300 min was an independent risk factor for postoperative CSA-AKI, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another tool for predicting the risk of AKI and improving individualized patient care is focused on identifying the genetic risk factors that might be involved [11], a decreased hemoglobin concentration during CPB surgery is an independent risk factor for AKI, with an effect cut-off value of <9 g/dL (<5.6 mmol/L) (OR, 1.16 per 1 g/dL decrease; 95% CI, 1.05-1.31; P = 0:018), which is not altered by systemic arterial oxygen saturation and pressure values. Other studies also support that the low hemoglobin concentration even within the normal range, as well as the nadir hemoglobin level, is associated with increased incidence of CPB-associated AKI [53,54]. Strategies that improve the hemoglobin concentration, such as the conservative use of red blood cell (RBC) transfusion, are recommended, since circulating free iron-mediated nephrotoxicity with hemolysis and free hemoglobin are likely to lead to AKI in patients undergoing cardiac surgery with CPB.…”
Section: Genetic Polymorphismsmentioning
confidence: 99%